2000
DOI: 10.1074/jbc.275.2.1391
|View full text |Cite
|
Sign up to set email alerts
|

Adozelesin Triggers DNA Damage Response Pathways and Arrests SV40 DNA Replication through Replication Protein A Inactivation

Abstract: The cyclopropylpyrroloindole anti-cancer drug, adozelesin, binds to and alkylates DNA. Treatment of human cells with low levels of adozelesin results in potent inhibition of both cellular and simian virus 40 (SV40) DNA replication. Extracts were prepared from adozelesintreated cells and shown to be deficient in their ability to support SV40 DNA replication in vitro. This effect on in vitro DNA replication was dependent on both the concentration of adozelesin used and the time of treatment but was not due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
45
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…12,26 This interaction is disrupted by UV, adozelesin and cisplatin and a correlation between RPA-p53-binding and RPA2 phosphorylation status has been observed. 33,34 RPA2 has been shown to undergo cell cycle-dependent and damage-induced phosphorylation, and although the consequences of this phosphorylation are unclear, it may influence RPA conformation, DNA-binding characteristics, and/or its interactions with other proteins. 33,34 In conclusion, the widespread expression of RPA1 and RPA2 proteins in colon carcinomas suggests that these proteins are implicated in colon cancer growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,26 This interaction is disrupted by UV, adozelesin and cisplatin and a correlation between RPA-p53-binding and RPA2 phosphorylation status has been observed. 33,34 RPA2 has been shown to undergo cell cycle-dependent and damage-induced phosphorylation, and although the consequences of this phosphorylation are unclear, it may influence RPA conformation, DNA-binding characteristics, and/or its interactions with other proteins. 33,34 In conclusion, the widespread expression of RPA1 and RPA2 proteins in colon carcinomas suggests that these proteins are implicated in colon cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 RPA2 has been shown to undergo cell cycle-dependent and damage-induced phosphorylation, and although the consequences of this phosphorylation are unclear, it may influence RPA conformation, DNA-binding characteristics, and/or its interactions with other proteins. 33,34 In conclusion, the widespread expression of RPA1 and RPA2 proteins in colon carcinomas suggests that these proteins are implicated in colon cancer growth. Moreover, their association with advanced stage, lymph node metastasis as well as their increased expression in metastatic sites supports a role in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several anti-cancer drugs have been identified that interact with the RPA complex (Liu et al, 2000;Peters et al, 2001). One of these, tirapazamine, is a hypoxia-activated cytotoxic agent which is currently in phase III clinical studies and has been localized to RPA2 (Peters et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Because RPA levels were similar in extracts of heated and non-heated cells and because RPA was relatively resistant to direct heat inactivation, we proposed that the observed response reflected the activation of a checkpoint that targeted and inactivated RPA. A regulatory role for RPA in DNA replication has also been suggested in cells exposed to ionizing radiation (31)(32)(33)(34)(35).…”
mentioning
confidence: 99%